2014
DOI: 10.5114/aoms.2014.43737
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review/Meta-analysis Interleukin-1B-31T/C promoter polymorphism and chronic obstructive pulmonary disease risk: a meta-analysis

Abstract: IntroductionThe role of interleukin (IL)-1β –31T/C promoter polymorphism in the pathogenesis of chronic obstructive pulmonary disease (COPD) has been studied with inconsistent results. This meta-analysis was performed to assess the association of IL-1β –31T/C promoter polymorphism with COPD susceptibility.Material and methodsPublished case-control studies from PubMed and China National Knowledge Infrastructure (CNKI) databases were retrieved. Data were extracted and pooled odds ratios (OR) with 95% confidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The present results suggest that miR-21 was upregulated in DLBCL tissues and its expression in non-GCB tissues was higher when compared with GCB tissues. These findings were consistent with the results from previous studies (24,25).…”
Section: Discussionsupporting
confidence: 83%
“…The present results suggest that miR-21 was upregulated in DLBCL tissues and its expression in non-GCB tissues was higher when compared with GCB tissues. These findings were consistent with the results from previous studies (24,25).…”
Section: Discussionsupporting
confidence: 83%
“…The interleukin-1 gene cluster has been mapped to the long arm of chromosome 2 and consists of three genes, IL-1α, IL-1β and IL-1 receptor antagonist genes, encoding IL-1α, IL-1β and IL-1 receptor antagonist proteins, respectively [ 42 ]. There are studies suggesting that some kinds of polymorphisms in the IL1B gene are associated with an increased risk of diseases such as chronic obstructive pulmonary disease [ 43 ] or chronic periodontitis [ 44 ]. In the experimental and clinical research, it has been demonstrated that administration of a receptor antagonist or immunoglobulins against IL-1β prevents the increase in IL-6 and TNF-α in inflammation, as well as decreasing the severity of inflammation [ 40 , 45 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the association between this polymorphism and prostate cancer risk remains conflicting. Meta-analysis is used to combine the previous results to yield the most reliable and comprehensive conclusion because the individual research was too minor to achieve a valid conclusion [ 47 , 48 ]. In this article, novel case-control studies from the last years were enrolled and a meta-analysis containing 9,720 prostate cancer patients and 9,710 controls from 25 independent case-control studies was performed.…”
Section: Discussionmentioning
confidence: 99%